Counting for preschool children (CPC) / Hazwani Ishak - Hazwani , Ishak (2002)
Multimedia interactive package has bring new diemnsion to the educational world. Lack of interactive learning package in English that focus on counting only give me an idea to develop multimedia system title Counting for Pre-school Children (CPC) as my final thesis project. The purpose of CPC package is to increase multimedia teaching method in the local market. It is develop so that it can bring the educational world to the more higher level by intoducing one efficent learning method that apply interactive multimedia concept. CPC package has 4 module as menu. The module are let’s learn, activity, quiz and exit. The system also contain additional module that is help to make the system more complete. The learning foundation for counting in this package contained in let’s learn module. Counting for Pre-school Children system use waterfall model to develop it. It is a suitable development model because it has separate process phases and easy to use. This system is develop using Macromedia Director MX that provide it own Lingo script. Other software are Macromedia Flash 5, Macromedia Flash MX, Ulead Cool 3D, Adobe Photoshop 7.0 and Sound Recorder. CPC system is hope to achieve it objectives and goals besides being quality teaching method.